(untitled) (Eurasian Research Bulletin, 2025)
This article reflects on the theoretical foundations of preparing teachers of the future pedagogical Technical School for professional activities. Feedback on the need to achieve the knowledge, qualifications, skills and professional competencies that future teachers should acquire in the process of preparation for professional activities, pedagogical abilities and pedagogical skills, and the importance of self-development and non-stop research during the course of conducting professional activities are presented.